Pentingnya atau Pengaruh Etos Kerja dan Etika serta Dampaknya terhadap Profesi dan Perkembangan Karir Seseorang di Dunia Kerja - Nayogy, Chasty Eva; Amalia, Restu; Andriani, Luthfi Nabila; Mimi, Denata Sere (Jurnal Bisnis Inovatif dan Digital, 2025)
This research examines the importance of work ethic and ethics in the professional world, as a strong work ethic and high ethical standards serve as a foundational guarantee for individual success in today's competitive job market. The study aims to determine how integrity, responsibility, diligence, and professionalism not only shape a person's reputation but also directly influence the quality of work and overall productivity. In the dynamic modern professional world, integrity, responsibility, and diligence are not merely theoretical knowledge; rather, sound judgment is also essential for maintaining personal reputation and credibility. Furthermore, a positive work ethos and ethics are proven to be key factors for professional advancement and long-term career development. This case study utilizes a qualitative method, where information is derived from observations and verbal descriptions. By analyzing the relationship between ethos and ethics, the study concludes that strategic investment in these areas can yield greater opportunities, job stability, and enhanced professional satisfaction, establishing them as invaluable assets in the global labor market.